Women-The Best of Creatures in World: Are They Upholding the Premise? - Rahman, Dr. Akim (Journal of Economics and Behavioral Studies, 2022)
Women are the best of creatures no matter what part of the world they reside in. However, the premise is being questioned because of the high rise of divorce rates in many parts of the modern- world where humankind behaves with a business mentality in work, life and activities without reservation. In reality, the collapse of marriage is not a sudden event. It happens at an onset moment. It is a process during which various factors lead to a decision- for divorce. The purpose of this study was to build a theory about the process of divorce, which can be suitable to all cultures or faiths without reservation. All factors involved in the process are categorized into two parts: Expectation-factors and Causal-factors. The net profit (NP) staying in the marriage is calculated based on the weight assigned by each spouse for each Expectation-factor. Net-loss (NL) is calculated based on the weight assigned by each spouse for each Causal-factor. The difference between NP and NL guides a spouse or both for a decision on opportunity correcting errors or living separately but no divorce or divorce. The findings of this study can be helpful to professionals gaining better knowledge on extending help for their reunion or smooth divorce approach for the betterment of both. It can further be helpful to authorities responsible for divorce prevention and improving marriage-relationship by counseling based on the result(s) of this study emphasizing their future plans. It can be helpful recovering wives’ or husbands’ shortcomings without letting the other party knows about them. This framework can be helpful to wives sharpening its qualities, which can be helpful upholding the premise, Women the best of the creature. Thus, the answer to the question posed in the title depends on who we ask.